Single-cell transcriptomic analysis reveals the immunosuppressive status of NK cell subpopulations in TNBC - Yang Liu; Wen-Ming Cao; Ying Jin; Weizhen Xu (PLoS ONE, 2026)
Triple-negative breast cancer (TNBC), lacking expression of the estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2), has clinical features that include high invasiveness, limited response to current immunotherapies, heightened risk of recurrence, and poorer overall prognosis. Central to these adverse clinical outcomes is the tumor microenvironment (TME), where the presence of immature natural killer (NK) cells with lower cytotoxic capacity has been associated with disease progression. Through a comprehensive analysis of publicly available single-cell transcriptomic data from breast cancer, we identified three NK cell subtypes within TNBC and non-TNBC tissues, named NK_XCL1, NK_FCGR3A, and NK_ISG15. Compared to non-TNBC, the presence and cytotoxic activity of NK_FCGR3A cells in TNBC were markedly diminished, primarily due to a substantial increase in the expression of inhibitory receptors like NKG2A (KLRC1). NK_ISG15 cells in TNBC show higher expression of type I interferon signaling genes. Through cell-type cross-talk analysis, we found that the feature of NK_FCGR3A cells in TNBC was mediated by myeloid cells with the HLA-E-KLRC1/HLA-E-CD94:NKG2A signal pathway. Notably, through integrating with public cancer transcriptomic data, we found higher expression of ISG15 is associated with poor prognosis, while higher expression of NK_FCGR3A signature genes is correlated with favorable prognosis. Collectively, these findings and the markers identified offer valuable insights into the mechanisms of immune evasion in TNBC, underscoring potential targets for developing therapeutic strategies that may improve patient outcomes.